OPTIMASI CUTTING STOCK PADA INDUSTRI PEMOTONGAN KERTAS DENGAN MENGGUNAKAN METODE INTEGER LINEAR PROGRAMMING (Studi Kasus di Bhinneka – Semarang) - Nurkertamanda, Denny; Saptadi, Singgih; Permanasari, Adhika (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2007)
In paper cutting industry, cutting stock problem (CSP) is a problem about how to cutting paper depends on quantity and specify of the demand. CSP related with dimension of pieces and rectangle which is use. In this research, we use one type dimension of rectangle and six type dimension of pieces and cutting all paper by two stage guillotine pattern. The major focus of this research is to formulate the paper cutting problem using integer linear programming. Cutting large objects into small pieces can be found in many industries. Inevitably, the cutting processes produce trim loss. On the rectangle we can put some different dimension of pieces then we can make certain pattern. The modification pattern have to produce minimum trim loss. Thus to develop optimal cutting pattern to reduce trim loss is the main purpose of this research. To reach that, we use branch and bound algorithm then continued with sensitivity analysis. From the research, we get optimum patten of paper cutting and quantity production for that pattern. Decision for quantity production depends on average demand every day. Beside that, we also give some alternative rules of production system which can take by the company. Keywords : Cutting stock problem, two stage guillotine pattern, branch and bound algorithm